Annual Plan 1998-99 Volume I Government of National Capital Territory of Delhi - Planning Commission (Planning Commission, 1998)
The principal task of planning in a Federal System is to evolve a shared vision and a shared commitment to the National objective of all round economic development. No development strategy can be successful unless each component of the economy works towards a common purpose with the full realization of the role that has to be played within over all structure of responsibilities.
Planning Department, Government of National Capital Territory of Delhi